The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1161/hc3101.093905
|View full text |Cite
|
Sign up to set email alerts
|

Phased Chest and Abdominal Compression-Decompression Versus Conventional Cardiopulmonary Resuscitation in Out-of-Hospital Cardiac Arrest

Abstract: Background-Several methods have been developed to improve the efficacy of mechanical resuscitation, because organ perfusion achieved with conventional manual resuscitation is often insufficient. In animal studies, phased chest and abdominal compression-decompression resuscitation by use of the Lifestick device has resulted in a better outcome compared with that of conventional resuscitation. In end-of-life patients, an increased coronary perfusion pressure was achieved. The aim of the present study was to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 24 publications
0
14
0
3
Order By: Relevance
“…A detailed description has been given elsewhere of the 2-tiered emergency system (EMS): a first-tier ambulance with emergency medical technicians on board equipped with automated external defibrillators (AEDs) and a second tier manned with an emergency physician. 10 On the basis of a questionnaire evaluated in a pilot study, all available bystanders and witnesses of the arrest were interviewed on site by the emergency physician. This questionnaire was used to obtain data on the logistics of EMS and demographics, as well as the patient's medical history, medication use, and any preceding signs or symptoms and their duration.…”
Section: Emergency System Structurementioning
confidence: 99%
“…A detailed description has been given elsewhere of the 2-tiered emergency system (EMS): a first-tier ambulance with emergency medical technicians on board equipped with automated external defibrillators (AEDs) and a second tier manned with an emergency physician. 10 On the basis of a questionnaire evaluated in a pilot study, all available bystanders and witnesses of the arrest were interviewed on site by the emergency physician. This questionnaire was used to obtain data on the logistics of EMS and demographics, as well as the patient's medical history, medication use, and any preceding signs or symptoms and their duration.…”
Section: Emergency System Structurementioning
confidence: 99%
“…In a study that consisted of a small series of cases, X-CPR produced higher coronary perfusion pressure than S-CPR (42). In a study with the Lifestick, a phased thoracic-abdominal active compression-decompression CPR device, no difference was detected compared with S-CPR in terms of ROSC, but it was reported that this technique could be advantageous for patients with asystole or pulseless electrical activity (48). Another study conducted with a small sample (49) did not report any statistically significant difference between using the Lifestick and applying S-CPR.…”
Section: Studies Conducted On the Effectiveness Of Mccdsmentioning
confidence: 98%
“…The larger adhesive pad is placed over the abdomen and the smaller over the anterior chest wall. An implementer compresses the two sides of the device just like a seesaw, applying pressure both on the chest and the abdomen alternately ( Figure 5b) (11,27,(48)(49)(50).…”
Section: Phased Thoracic-abdominal Active Compressiondecompression Cpmentioning
confidence: 99%
“…Tierexperimentelle Untersuchungen zeigten Vorteile dieser Technik [162]. In einer klinischen Untersuchung konnte die Überlebenschan-ce jedoch nicht verbessert werden [19]. Mithilfe druckluftbetriebener mechanischer Geräte (Thumper®) zur Durchführung von Thoraxkompressionen konnte eine Verbesserung der Hämody-namik in CPR-Laborstudien gezeigt werden.…”
Section: Nichtempfohlene Techniken Der Kardiopulmonalen Reanimationunclassified